Convergence Research for Emerging Zoonoses. Issue 6 (June 2021) - Talbot, Benoit; Kulkarni, Manisha A.; Colautti, Robert I.
Abstract : Global emergence of vector-borne and zoonotic diseases presents a rapidly growing 'wicked' problem. We outline the need for a transdisciplinary research program that is grounded in ecological and evolutionary theory but integrates fundamentally with research perspectives spanning the health, social, and natural sciences.